2019
DOI: 10.1002/erv.2700
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the interpersonal model of binge eating over the course of treatment

Abstract: The current study examined the interpersonal model of binge eating, which posits that interpersonal problems lead to negative affect which results in binge eating, over the course of two psychotherapy treatments (interpersonal psychotherapy and cognitive behavioral therapy) in 162 adults with binge-eating disorder. A series of longitudinal simple mediation analyses preliminarily showed that treatment addresses the mechanisms of the interpersonal model of binge eating as theoretically proposed in predicting red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…However, the prevalence observed in our sample is higher than the prevalence observed in treatment‐seeking patients with BED in a study using national registry data (Welch et al., 2016), suggesting that the exclusion criteria in our study may have not substantially impacted the proportion of participants with PTSD in our sample. The sample composition represents another limitation of the present study, as, consistent with many other BED treatment samples (e.g., Karam, Eichen, Fitzsimmons‐Craft, & Wilfley, 2020; Serra et al., 2020), participants were primarily Caucasian, female, and well educated, thereby limiting generalizability to other samples. Despite these limitations, however, this study provides valuable information on the role of trauma in relation to BED treatment outcomes.…”
Section: Discussionmentioning
confidence: 89%
“…However, the prevalence observed in our sample is higher than the prevalence observed in treatment‐seeking patients with BED in a study using national registry data (Welch et al., 2016), suggesting that the exclusion criteria in our study may have not substantially impacted the proportion of participants with PTSD in our sample. The sample composition represents another limitation of the present study, as, consistent with many other BED treatment samples (e.g., Karam, Eichen, Fitzsimmons‐Craft, & Wilfley, 2020; Serra et al., 2020), participants were primarily Caucasian, female, and well educated, thereby limiting generalizability to other samples. Despite these limitations, however, this study provides valuable information on the role of trauma in relation to BED treatment outcomes.…”
Section: Discussionmentioning
confidence: 89%
“…In such cases, interpersonal therapy can assist people with eating disorders (e.g., BED) to create relationships that provide esteem and positive emotional connection so that they do not rely on eating disorder behaviors to regulate their emotions 75 . Additionally, a therapist using interpersonal therapy can investigate people's life history to identify problematic interpersonal areas (e.g., grief, interpersonal role disputes, role transitions, and interpersonal deficits) associated with the onset and maintenance of binge eating 76 . After the identification of these areas, the therapist can help people with BED with the implementation of strategies to make long‐term modifications in the identified areas 76 …”
Section: Additional Psychological Therapies For Bedmentioning
confidence: 99%
“…75 Additionally, a therapist using interpersonal therapy can investigate people's life history to identify problematic interpersonal areas (e.g., grief, interpersonal role disputes, role transitions, and interpersonal deficits) associated with the onset and maintenance of binge eating. 76 After the identification of these areas, the therapist can help people with BED with the implementation of strategies to make long-term modifications in the identified areas. 76 Some studies suggest that interpersonal therapy can be as effective as CBT in the treatment of BED and can be particularly useful for people with BED and certain psychological characteristics.…”
Section: Interpersonal Therapy For Bedmentioning
confidence: 99%
“…Attachment Theory (Bowlby, 1969) proposes that, in response to interactions with their early caregivers, children build internal working models, which influence how they conduct and perceive future interpersonal relationships and how they regulate and express emotion. It has been suggested that individuals experiencing BED have developed unhelpful ways of interacting with others to feel safe and avoid being rejected or abandoned by others (Wonderlich et al , 2001), providing support for the Interpersonal Model, which suggests that difficulties with social functioning or interpersonal problems cause negative affect, which in turn leads to binge eating (Karam et al , 2020). Attachment Theory can be utilised as a framework for measuring psychotherapy outcomes (Mallinckrodt, 2000) and this is helpful in relation to BED, since interpersonal problems have been found to contribute to the maintenance of BED symptomology (Arcelus et al , 2013; Miniati et al , 2018; Ung et al , 2017).…”
Section: Introductionmentioning
confidence: 99%